2020
DOI: 10.21037/atm.2020.03.109
|View full text |Cite
|
Sign up to set email alerts
|

Application of the modified stented elephant trunk procedure in type B aortic dissection

Abstract: Background: Considering the progressive nature of complicated Stanford type B aortic dissection (TBAD), operation must anticipate the need for later interventions. Recently we have used a modified stent elephant trunk (SET) procedure to treat these patients. And we review the indications, considerations for planning, and operative details for this this modified SET procedure. Methods: Ten patients (seven males and three females) with complicated TBAD underwent a modified SET procedure in Anzhen Hospital, Beiji… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…By quantifying the impact of LSA sealing on hemodynamic parameters during TEVAR virtually, blood flow was investigated in a type B aortic dissection undergoing ISF-TEVAR with LSA reconstruction ( 25 ). The amount of blood flow crossing the LSA was between 3.52 and 5.28% in healthy young humans, which should vary from 4.01 to 6.14% under ideal conditions ( 26 ). However, the present outcome showed that merely 2.36% of the total inlet flow was assigned to the fenestration LSA, which was lower than expected.…”
Section: Discussionmentioning
confidence: 99%
“…By quantifying the impact of LSA sealing on hemodynamic parameters during TEVAR virtually, blood flow was investigated in a type B aortic dissection undergoing ISF-TEVAR with LSA reconstruction ( 25 ). The amount of blood flow crossing the LSA was between 3.52 and 5.28% in healthy young humans, which should vary from 4.01 to 6.14% under ideal conditions ( 26 ). However, the present outcome showed that merely 2.36% of the total inlet flow was assigned to the fenestration LSA, which was lower than expected.…”
Section: Discussionmentioning
confidence: 99%